2023
DOI: 10.2196/41182
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Digital Health on Smoking Cessation

Abstract: Background Smartphones have become useful tools for medicine, with the use of specific apps making it possible to bring health care closer to inaccessible areas, continuously monitor a patient's pathology at any time and place, promote healthy habits, and ultimately improve patients’ quality of life and the efficiency of the health care system. Since 2020, the use of smartphones has reached unprecedented levels. There are more than 350,000 health apps, according to a 2021 IQVIA Institute report, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Mobile health apps have shown effectiveness in promoting positive health behaviors and improving outcomes across various health domains [12], [24]- [27] Mellitus patients [28]. Additionally, a randomised controlled trial targeting older adults with chronic conditions and low health literacy found that a customised mobile app could improve patient activation, self-efficacy and health-related quality of life [29].…”
Section: Effectiveness Of Mobile Health Appsmentioning
confidence: 99%
“…Mobile health apps have shown effectiveness in promoting positive health behaviors and improving outcomes across various health domains [12], [24]- [27] Mellitus patients [28]. Additionally, a randomised controlled trial targeting older adults with chronic conditions and low health literacy found that a customised mobile app could improve patient activation, self-efficacy and health-related quality of life [29].…”
Section: Effectiveness Of Mobile Health Appsmentioning
confidence: 99%
“…The quit rate for smoking reported by previous literature in developed countries showed that self-reported smoking cessation rate was about 19% for 28 days or longer [ 12 ], while another study reported the quit rate of 13% via the use of mobile apps [ 13 ]. Quitting smoking can be a difficult challenge that sometimes requires many attempts before success is achieved, nicotine dependence is a complex disorder [ 14 ]. Data privacy and security of apps is also one of the concern by the smoking quitters followed by difficulty in locating effective, operational apps that safeguard user privacy [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, many people still find it difficult to quit [ 25 ], despite the well-known associated risks with smoking. Fortunately, the development of digital tools for tobacco cessation has made it easier for individuals to quit smoking and maintain abstinence [ 14 ]. These digital tools can take various forms, including mobile apps, web-based programs, and social media platforms, among others.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, mobile apps collect data from a variety of sources, including medical devices and wearable devices, which are then integrated into smartphone-based apps to help promote healthy behaviors in patients through monitoring and advice 5) . Mobile apps constitute a promising approach to disease management for patients with NCDs 6) , providing personalized support anytime, anywhere, and facilitating communication with healthcare providers (HCPs) [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%